Bridging the Research-Practice Gap: Research Translation and/or Research Transformation (Alberta Journal of Educational Research, 2008)
The issue of the “research-practice gap”—the problematic relationship between research in education and educational practice—has been widely reported in the literature. This critical literature review explores some of the causes and features of the gap and suggests some possible approaches for addressing it. These solutions involve changes in the practices of both researchers and practitioners.